An unusual thionyl chloride-promoted C−C bond formation to obtain 4,4'-bipyrazolones - Eller, Gernot A (Beilstein J Org Chem, 2018)
Dialkyl 5,5'-dioxo-4,4'-bipyrazole-4,4'-dicarboxylates are readily obtained by the reaction of 5-hydroxypyrazole-4-carboxylates in refluxing thionyl chloride. The obtained diesters can be transformed into the corresponding 4,4'-bipyrazoles via alkaline hydrolysis and subsequent decarboxylation. Detailed NMR spectroscopic investigations ((1)H, (13)C, (15)N) were undertaken with all products prepared. Moreover, the structure of a representative 5,5'-dioxo-4,4'-bipyrazole-4,4'-dicarboxylate was confirmed by X-ray crystal structure analysis.